The Relationship Between Length of Hemodialysis Therapy and age With Quality of Life in Chronic Kidney Failure Patients at PKU Muhammadiyah Gamping Hospital - Puspa Jelita Kartika Utami; Sigit Harun; Diyah Candra Anita (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Chronic kidney failure in the end stage requires kidney replacement therapy in the form of haemodialysis. Haemodialysis is not to cure but as a replacement therapy for kidney function to clean the blood from various substances that cannot be excreted naturally by the kidneys which must be done for life. Chronic kidney failure patients undergoing haemodialysis can cause life changes that will affect the patient’s quality of life. This study aims to determine the relationship between the duration of haemodialysis therapy and age and the quality of life in chronic kidney failure patients at PKU Muhammadiyah Gamping Hospital. This study employed a descriptive correlation study with a cross-sectional method. The study population was 165 patients with a sample of 115 respondents. The instrument to determine the quality of life was the Kidney Disease Quality of Life (KDQOL) Questionnaire and interviews were done to determine the age and duration of haemodialysis therapy. The results of statistical tests using the Kendall Tau test showed a p-value> 0.05, which is 0.059 for the test of the duration of haemodialysis therapy with quality of life. Thus, it can be concluded that there is no significant relationship between the duration of haemodialysis therapy and quality of life in chronic kidney failure patients at PKU Muhammadiyah Gamping Hospital. Statistical tests for age with quality of life using the Kendall Tau test showed a p-value> 0.05, which is 0.694. Therefore, it can be concluded that there is no significant relationship between age and quality of life in chronic kidney failure patients at PKU Muhammadiyah Gamping Hospital.